Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1534/g3.113.009621
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Screen for Functional Partners of Condensin in Fission Yeast

Abstract: Mitotic chromosome condensation is a prerequisite for the accurate segregation of chromosomes during cell division, and the conserved condensin complex a central player of this process. However, how condensin binds chromatin and shapes mitotic chromosomes remain poorly understood. Recent genome-wide binding studies showing that in most species condensin is enriched near highly expressed genes suggest a conserved link between condensin occupancy and high transcription rates. To gain insight into the mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…; Robellet et al . ; Nikalayevich & Ohkura ). The relevance of these proteins and Ki67 is also worth examining.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Robellet et al . ; Nikalayevich & Ohkura ). The relevance of these proteins and Ki67 is also worth examining.…”
Section: Discussionmentioning
confidence: 99%
“…; Robellet et al . ; Nikalayevich & Ohkura ). Although recent studies have shown that mitotic chromosome‐like structures can be reconstituted in vitro with only six defined factors (Shintomi et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these phenotypes may result from the reduced expression of specific genes, a recent study rather points to a direct role of RSC and nucleosome eviction in condensin loading and chromosome condensation (Toselli-Mollereau et al 2016). A genetic screen for functional partners of condensin in fission yeast (synthetic lethality with cut3 - 477 that encodes a condensin ATPase subunit) identified alleles of arp9 and snf21 that both showed high frequency of chromatin bridges in anaphase (Robellet et al 2014). Further analyses revealed the preferred localization of condensin at, or near NDR and that increased nucleosome occupancy upon RSC downregulation is sufficient to decrease condensin binding.…”
Section: A Key Role Of Rsc In Mitotic Chromosome Condensationmentioning
confidence: 99%
“…However, among individual otr3L repeats there is no apparent bias in Cut3 distribution, suggesting additional factors may be required to establish position-dependent heterochromatin organizations. Cohesins and other chromatin remodeling complexes are possible candidates to control the position effect within the peri-centromeric repeat array (Mizuguchi et al, 2014; Robellet et al, 2014). …”
Section: Mechanisms Regulating Position Effect In Tandem Repeatsmentioning
confidence: 99%